Review of Rare-earth Ion Doped Phosphors for White Light Generation - Bommareddi, Rami Reddy (New Trends in Physical Science Research Vol. 8, 2022)
This review is focused on the design of phosphor coatings for diode pumped solid state lighting applications. A brief summary is provided on the historical developments of light bulb evolution. A discussion is provided on the suitability of rare-earth doped phosphor materials for white light generation. Color coordinates and color temperatures are measured for several materials, including crystals and glasses embedded with rare-earth ions. Spectroscopic results of Sm, Dy, Tb, Eu and Dy ions, obtained under 405 and 375 nm diode laser excitations are given. Analysis of the data indicated whether a phosphor coated diode emits warm white light, day light or cool white light, is dependent on the type of dopant ions in the phosphor material and pump wavelength. Our studies indicate that Tb, Eu or Dy doped halide crystals generate white light under diode laser excitation. However, glasses embedded with Sm, Dy, and Tb generate white light or warm white light.